Home Hazards With Fear of Falling: Findings From the Baseline Study of the Malaysian Elders Longitudinal Research (MELoR) - Romli, Muhammad Hibatullah; Mackenzie, Lynette; Lovarini, Meryl; Clemson, Lindy; Tan, Maw Pin (Frontiers in Public Health, 2021)
Background: Fear of falling (FoF) is a common issue among older people, impacting on psychological health, functional performance and mortality. Many factors associated with fear of falling have been investigated but little is known about the role of home hazards. Home hazards can be due to unsafe environmental and functional features. This study is aims to evaluate the association between home hazards with fear of falling among community-dwelling individuals aged 55 years and over. Methods: Baseline data with 1,489 older individuals from the Malaysian Elders Longitudinal Research (MELoR) study were analyzed. Home visits for interview and observations in the home were conducted with the participants. FoF was established with a single-item question and home hazards with the Home Falls and Accidents Screening Tool (HOME FAST). Results: The majority (76.4%) of older participants experienced FoF. The history of falls was not associated with FoF (p = 0.868), but FoF was associated with participants limiting their daily activities (p < 0.001). Home hazards were less likely (p = 0.023) and functional issues were more likely (p < 0.001) to be associated with a high degree of FoF. However, both home hazards domains were not associated with activity restriction due to FoF. Conclusions: Education about home hazards from the perspective of person-environment interaction may encourage home hazards management and reduce FoF which should be evaluated in future studies.